Training On Dengue Haemorrhagic Fever Surveillance System And Case Mapping For Public Health Center Level Dengue Hemorrhagic Fever Program Managers In Bogor City In 2022 - Iska Beritania Sinulingga; Tri Yunis Miko Wahyono; Bai Kusnadi (Jurnal EduHealth, 2023)
Background Behind : Bogor City has The incidence rate is 21.4 per 100,000 population, but the CFR is sufficient tall by 2.49%. So from That need exists enhancement knowledge about surveillance of DHF program holders in Bogor City in 2022. Method : Study design in research dengue operations is studies non-experimental pre-test and post-test design. Primary data begins from pretest-posttest results to DHF program manager with use questionnaire while Skills mapping taken from sheet observations that have made. While the secondary data obtained from results analysis Bogor City Health Office profile. Data analysis was performed in a manner univariate, bivariate and multivariate. Result: yes difference knowledge Community Health Center DBD program holders after done training in matter knowledge DHF surveillance (Pvalue < 0.05). There is difference enhancement Skills in do mapping DHF cases in DHF program holders at Puskesmas after done training in do mapping with use application ( Pvalue <0.05), and presence enhancement in do data interpretation and determine stratification area DHF cases (Pvalue <0.05). Conclusion: improvement knowledge and skills DHF program holders are carried out with use appropriate intervention , so DHF program holders can do system good surveillance in prevention and control DHF.